S. Typhi derived vaccines and a proposal for outer membrane vesicles (OMVs) as potential vaccine for typhoid fever. (September 2021) - Haque, Shabirul; Swami, Pooja; Khan, Azhar
Abstract: Typhoid fever is a serious systemic infection caused by Salmonella Typhi ( S. Typhi ), spread by the feco-oral route and closely associated with poor food hygiene and inadequate sanitation. Nearly 93% of S. Typhi strains have acquired antibiotic resistance against most antibiotics. Vaccination is the only promising way to prevent typhoid fever. This review covers the nature and composition of S. Typhi, pathogenecity and mode of infection, epidemiology, and nature of drug resistance. Several components (Vi-polysaccharides, O-antigens, flagellar antigens, full length OMPs, and short peptides from OMPs) of S. Typhi have been utilized for vaccine design for protection against typhoid fever. Vaccine delivery systems also contribute to efficacy of the vaccines. In this study, we propose to develop S. Typhi derived OMVs as vaccine for protection against typhoid fevers. Highlights: Typhoid fever is a serious health infection caused by Salmonella Typhi. Nearly 93% of S. Typhi strains have acquired antibiotic resistance with most of the antibiotics. Vaccination is the only promising way to prevent typhoid fever. This review covers the nature of S. Typhi, pathogenecity and mode of infection, epidemiology, and nature of drug resistance. We also proposed a novel approach of vaccine development and optimization of OMVs, derived from S. Typhi.